Research Progress for RNA Modifications in Physiological and Pathological Angiogenesis - Chen, Hui-Ming; Li, Hang; Lin, Meng-Xian; Fan, Wei-Jie; Zhang, Yi; Lin, Yan-Ting; Wu, Shu-Xiang (Frontiers in Genetics, 2022)
As a critical layer of epigenetics, RNA modifications demonstrate various molecular functions and participate in numerous biological processes. RNA modifications have been shown to be essential for embryogenesis and stem cell fate. As high-throughput sequencing and antibody technologies advanced by leaps and bounds, the association of RNA modifications with multiple human diseases sparked research enthusiasm; in addition, aberrant RNA modification leads to tumor angiogenesis by regulating angiogenesis-related factors. This review collected recent cutting-edge studies focused on RNA modifications (N6-methyladenosine (m6A), N5-methylcytosine (m5C), N7-methylguanosine (m7G), N1-methyladenosine (m1A), and pseudopuridine (Ψ)), and their related regulators in tumor angiogenesis to emphasize the role and impact of RNA modifications.